New combination and typifications of names of Caribbean species of Myrcia sect. Calyptranthes (Myrtaceae) - Alvarenga Braga, João Marcelo; Fernandes, Thiago; C. St. E. Campbell, Keron; Prado, Jefferson; J. Lucas, Eve (Phytotaxa, 2022)
A new combination is presented in Myrcia, and the names Calyptranthes rigida Swartz and Calyptranthes fawcettii Krug & Urban are typified.